The consumers of green products: The case of Romanian Moldavia counties - Mario Pagliacci; Adriana Manolică; Teodora Roman; Gabriela Boldureanu (Amfiteatru Economic Journal, 2019)
Being green is not a trend, as it is not a luxury. Being green has become a necessity. Sustainable consumption, the impact of our own consumption on the environment, the legacy we leave to future generations become goals and guide behaviors. Our research starts from a three-month longitudinal analysis of the consumption of 80 families (of which 40 with children up to 14 years, respectively 40 without children) from the eight counties in Moldavia - Romania, in order to explore if we can talk about a green consumption of the population in urban areas. Being exploratory, the research presents a perspective offered by the panel of subjects selected by the snowball method. The selected respondents are the ones who make the decision to buy food in their family. Ten categories of foods were selected, for each obtaining consumption data, motivations and behaviors in order to obtain the weight in which green foods are included in the consumption. The research findings show that the main green products consumers are women and children. Most of those products don't come from supermarket or specialized stores, but from their own household, from their parents or grandparents or they are purchased from the street market. Romanian do not trust the big commercial chains, but in peasants, small or well-known entrepreneurs. Being more expensive, green products are still considered to be a luxury, but there is an increase in consumption, especially after the correct awareness of the difference between them and common products.
Keywords: D13; Q56; Q57; R21; 330; green/organic/bio products; green consumers; Y Generation families; Romania